Chemical, biological, radiological, nuclear and explosive (CBRNe) events: Systematic literature review of evacuation, triage and decontamination for vulnerable people. Issue 2 (5th August 2019) - Hignett, Sue; Hancox, Graham; Edmunds Otter, Mary
Abstract : Purpose: The purpose of this paper is to systematically review published literature for the research question "what issues are considered (and changes made) for vulnerable groups as part of the chemical, biological, radiological, nuclear or explosive (CBRNe) response for casualty collection, decontamination, triage and casualty clearing processes?". Design/methodology/approach: Seven-stage framework from the PRISMA statement for research question, eligibility (definition), search, identification of relevant papers from title and abstract, selection and retrieval of papers, appraisal and synthesis. Data sources: Medline, Embase, Cochrane Library, Web of Science, Scopus (Elsevier), Chemical Abstracts, Assia (Proquest), Sociological abstracts (Proquest), Cinahl, HMIC, Health business elite, PsycInfo (ebsco), PILOTS (Proquest) and supplemented by other search strategies (e.g. exploding reference lists). The included references were critically appraised using the mixed methods appraisal tool (MMAT). Findings: Results: 1, 855 papers were returned from the literature search, of which 221 were screened by abstract and 48 by full paper. In total, 11 papers were included for appraisal, of which three achieved a quality score of 50 per cent or over. The papers were categorised into three phases on CBRNe response; evacuation, triage and decontamination. Research limitations/implications: The limitations of the search process included the use of emerging exclusion criteria. This may have excluded research that would provide more information in some topic areas but it was felt necessary to set a high publication standard for inclusion to generate trustworthy results and recommendations. The MMAT appraisal tool has been validated for different study types and provided a useful categorisation approach for critical appraisal, albeit resulting in only three included studies. Future reviews could include papers published in a wider range of languages to include research from non-English sources. Practical implications: These evidence-based results should be used by practitioners to review current operational policies for vulnerable people and plan future improvements. Evacuation accessibility can be described as characteristics for exit, route and obstacles. This takes a systems approach to consider how building planning and layout can have implications for safety critical but low frequency events. Decontamination recommendations include: at least one additional re-robe section per mass decontamination unit and adaptations to the decontamination plan including accessible equipment for non-ambulatory individuals; and additional (specialist) staff in the decontamination team (sign language, interpreters and physical therapists). Originality/value: Although very little new medium/high quality research is available, the findings are summarised as considerations for building design (route choice and information), communication (including vision, hearing and language differences) and the composition of the response team. It is suggested that evidence-based practice from other care domains could be considered (patient movement and handling) for fire service and ambulance guidelines.